Defining components of social interaction for Indian public open space - Shafique , Adiba; Abdul Majid, Roshida (International Journal of Psychosocial Rehabilitation, 2020)
Improving public open space is becoming one of the prerequisites for effective future of public life in cities. The potential of social interaction attributes, which are one of the predominant factors of public open space, is often neglected in India. The factors of social interaction varies according to the context due to variation in culture, demography, social norms, etc. This study examines the factors of social interaction of Public open space in Indian context for making successful Indian public open space. The research has been twofold, first, literature review has been accomplished through which factors of social interaction has been derived. Based on obtained factors, questionnaire survey has been performed over three selected sites of South Delhi. In second section, data screening has been done, followed by the Cronbach’s alpha for checking reliability of each item and exploratory factor analysis using IBM SPSS plus confirmatory factor analysis using IBM Amos for confirming the validity of data. In conclusion, considering the listed factors that are users need, user behaviour and social activity are the significant components of social interaction for promoting effective Public open space in Indian context.